2019
DOI: 10.2478/amns.2019.1.00020
|View full text |Cite
|
Sign up to set email alerts
|

Intrachromosomal regulation decay in breast cancer

Abstract: Biological systems exhibit unique phenotypes as the result of the expression of a genomic program. The regulation of this program is a complex phenomenon, wherein different regulatory mechanisms are involved. The deregulation of this program is at the centre of the emergence of diseases such as breast cancer. In particular, it has been observed that coregulation patterns between physically distant genes are lost in breast cancer.In this work, we present a systematic study of chromosome-wide gene coregulation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…decay in all cancer phenotypes is similar to that showed by our group for Basal breast cancer (43). There, co-expression strength diminished with distance in an exponential-like form.…”
Section: Co-expression Decay Associated To Distance Is Specific For Esupporting
confidence: 88%
“…decay in all cancer phenotypes is similar to that showed by our group for Basal breast cancer (43). There, co-expression strength diminished with distance in an exponential-like form.…”
Section: Co-expression Decay Associated To Distance Is Specific For Esupporting
confidence: 88%
“…The ANOVA table results are presented in Supplementary Table 1, which confirms the distance-dependent decay in breast cancer subtypes (P <1e-4)). The shape of this decay in all cancer phenotypes is similar to that showed by our group for basal breast cancer [31]. There, co-expression strength diminished with distance in an exponential-like form.…”
Section: Cis-/trans-imbalance Is a Common Feature In Breast Cancer Susupporting
confidence: 85%
“…Previously [6][7][8], we observed that in breast cancer, trans-(inter-chromosome) gene interactions are more scarce and weaker in cancer samples compared to the healthy phenotype. Furthermore, in breast cancer, cis-interactions become stronger, however, this is strongest between physically close genes, and this gene correlation strength decays with the distance.…”
Section: Spatial Anomalies In Cancer-associated Grpsmentioning
confidence: 83%
“…Following previous work [7], we define a gene regulatory program (GRP) as a graph G[I(X i , X j )] of all the mutual information functions for a given empirical transcriptomics sampling space Ω. It can be shown that G[I(X i , X j )] is indeed a Markov random field [11,12] considering mutual information distributions under the pairwise sufficiency assumption [13].…”
Section: An Information Theoretical Approach To Gene Regulatory Programsmentioning
confidence: 99%
See 1 more Smart Citation